Association of histamine N-methyltransferase Thr105Ile polymorphism with Parkinson's disease and schizophrenia in Han Chinese: a case-control study. - Xinglong Yang; Chuanxin Liu; Jinxiang Zhang; Hongying Han; Xiuyan Wang; Zhoulin Liu; Yanming Xu (PLoS ONE, 2015)
Parkinson's disease (PD) and schizophrenia (SCZ) are frequent central nervous disorders that have unclear etiologies but that show similarities in their pathogenesis. Since elevated histamine levels in the brain have been associated with PD and SCZ, we wanted to explore whether the Thr105Ile substitution in the histamine N-methyltransferase gene (HNMT-Thr105Ile), which impairs histamine degradation, is associated with either disease. We used the ligase detection reaction to genotype a case-control cohort of Han Chinese patients with PD or SCZ and healthy controls at the HNMT-Thr105Ile locus. The Ile allele was associated with reduced risk of PD (OR 0.516, 95% CI 0.318 to 0.838, p = 0.007) and of SCZ (OR 0.499, 95% CI 0.288 to 0.865, p = 0.011). Genotype frequencies and minor allele frequencies were similar between patients and controls when we compared males with females or early-onset patients with late-onset ones. Genotype and allele frequencies were not significantly different between PD patients with dyskinesia and PD patients without dyskinesia. Our results suggest that the heterozygous Thr/Ile genotype at the HNMT-Thr105Ile locus and the minor Ile105 allele protect against PD and SCZ in Han Chinese.